ANALISIS KATA KUNCI ARTIKEL JURNAL KESEHATAN LINGKUNGAN INDONESIA - ROCHANI NANI RAHAYU; SENSUSIYATI (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
Descriptive analysis was performed on keywords used in the Indonesian Jurnal Teknologi Kesehatan Lingkungan 2017 - 2019 period. Data were downloaded from the site addresshttp://ejournal.undip.ac.id/index.php/jkli, then the data obtained is presented in tabular form. The results of the study and conclusions show that during 2017 - 2019 , a total of 46 articles have been published, and 165 keywords. The most keywords are keywords consisting of two words, 82 (49.69%), and the least keywords are consisting of four or more words, namely 5 (3,055%). It found that some keywords are not in Indonesian languange, some keywords use abbreviations, combinations of abbreviations and words, keywords use the name of the city / district / province, most research topics are about Filariasis